Career decision self-efficacy based on gender and socioeconomic status of university students in Indonesia - Cahyawulan, Wening; Fazny, Bella Yugi (Universitas Islam Negeri Raden Intan Lampung, 2022)
Overseas students with various gender backgrounds and socioeconomic statuses face various challenges in cultural adaptation in higher education. Hence, it is not uncommon for overseas students to experience stress which affects their career decision self-efficacy. The aim of this study was to provide an overview of overseas students’ career decision self-efficacy, which is influenced by socioeconomic status and gender. Measurements were carried out using the career decision self-efficacy-short form (CDSE-SF) which has been adapted in Indonesian. Respondents in this study amounted to 154 overseas students at universities all across Indonesia. The research method used was comparative research with descriptive statistics (mean and standard deviation) and non-parametric statistics (Spearman and Mann-Whitney U) analysis techniques. The results showed that the highest scores were sequentially in the domains of self-appraisal, goal selection, planning, occupational information, and problem-solving. In the correlation analysis and comparative test, it can be seen that there is no relationship between students’ socioeconomic status and career decision self-efficacy and there is no difference based on gender. The results of the research discussion indicated that family support, acculturation, and career-related training were important in increasing career decision self-efficacy.